Pengaruh Kodifikasi ICD 10 dan ICD 9 CM Terhadap Klaim JKN Rawat Inap di RSUD Dr. Soekardjo Kota Tasikmalaya Tahun 2018 - Arief Tarmansyah Iman; Diana Barsasela (Jurnal Persada Husada Indonesia, 2019)
Data sources to be entered into the INA-CBGs application come from medical records summarized in medical resumes, namely diagnosis data and actions / procedures, and if needed can be seen in the medical record file. Inappropriate codification can have an impact / influence on the amount of the output rate of the INA-CBG system, the study was conducted at Dr. Soekardjo, Tasikmalaya City. The study was conducted for 6 months, namely May - October 2018. The purpose of the study was to analyze the effect of the accuracy of the ICD 10 and 9CM ICD codification on claims (INA-CBGs code and INA-CBGs rates) JKN Hospitalized at Dr. RSUD Soekardjo, Tasikmalaya City in 2018. The sample in this study is a medical resume on the file of claims for inpatient care for Dr. RSUD Hospital. Soekardjo, Tasikmalaya City in the period of May 1, 2018 to May 30, 2018. The population is 1528, while the sample is 94. The results of the study indicate that the incorrect diagnosis code is 24 files (25.53%). Whereas the incorrect 9CM ICD code is 21 files (22.34%). The results recoding of 13 files of ICD (13.83%) underwent changes in the code and tariff of INA-CBGs, while the results of reprocessing using results 9CMrecoding ICD revealed that 17 codes (18.09%) experienced changes in the code and tariff of INA-CBGs. The statistical test using Chi Square shows that the change in ICD 10 code towards changes in the code and tariff of INA-CBGs has a significant effect. The hypothesis is the influence of the accuracy of the ICD 10 code on the INA-CBGs code on JKN Claims accepted. Likewise, the results of the chi square test show that the change in the 9 CM ICD code to changes in the INA-CBGs Code and the INA-CBGs rates significantly influence. Hypothesis There is an influence of the accuracy of the ICD9CM code on the INA-CBGs code and tariff on JKN Claims in Dr. Soekardjo, Tasikmalaya City in 2018 was accepted.